Optimising Law Enforcement Against Money Laundering Offences - Pribadi Prasaja; H. Abdul Razak (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
White-collar crime has developed to a transnational level that no longer recognises the territorial boundaries of the state. The form of crime is also increasingly sophisticated and neatly organised, making it difficult to detect. Criminals always try to save money from their crimes through various means, one of which ismoney laundering. In this way, they try to launder illegally obtained money into a form that looks legal. With this laundering, criminals can hide the true origin of the funds or money from the crimes they commit. This research is focused on library studies or document studies, because this research is mostly carried out on secondary data, and Primary Data as a complement, the data to be obtained in this study are collected by means of: Library research The library material referred to consists of primary legal materials, namely laws and regulations related to the title of this research and the Criminal Code. Similarly, secondary legal materials are studied in the form of scientific works of experts including research results (including theses and dissertations) related to the title of the researcher and using Qualitative Data.